The Role of Principal’s Academic Supervision in Encouraging the Development of Teachers’ Creativity and Innovation: An Integrated Literature Review - Wahyuni, Ayu Sri; Topan, Oktapian; Safitri, Inke; Ahyani, Nur; Effendi, Darwin (Journal of Social Work and Science Education, 2025)
The purpose of this article is to investigate the strategic role of academic supervision played by principals in encouraging teacher creativity and innovation. This study used a Systematic Literature Review (SLR) of fifteen scientific articles from 2021 to 2025. The results showed that planned, professional, and needs-based academic supervision can improve teacher motivation and professionalism, as well as their ability to create innovative and creative learning. Supervision approaches such as coaching, transformational, collaborative, and clinical have proven effective in helping teachers create learning methods that are in accordance with the times. However, limitations of time, facilities, and teacher readiness hinder the implementation of supervision. Therefore, policies and ongoing training that support principals to improve their capacity as educational controllers are needed. It is hoped that this study will provide theoretical and practical knowledge on how to create a school culture that supports innovation and learning quality. Findings inform policy design for principal training programs.